Intrinsically disordered enamel matrix protein ameloblastin forms ribbon-like supramolecular structures via an N-terminal segment encoded by exon 5 - Wald, Tomas; Osickova, Adriana; Sulc, Miroslav; Benada, Oldrich; Semeradtova, Alena; Rezabkova, Lenka; Veverka, Vaclav; Bednarova, Lucie; Maly, Jan; Macek, Pavel; Sebo, Peter; Slaby, Ivan; et al. (The Journal of biological chemistry, 2013)
Tooth enamel, the hardest tissue in the body, is formed by the evolutionarily highly conserved biomineralization process that is controlled by extracellular matrix proteins. The intrinsically disordered matrix protein ameloblastin (AMBN) is the most abundant nonamelogenin protein of the developing enamel and a key element for correct enamel formation. AMBN was suggested to be a cell adhesion molecule that regulates proliferation and differentiation of ameloblasts. Nevertheless, detailed structural and functional studies on AMBN have been substantially limited by the paucity of the purified nondegraded protein. With this study, we have developed a procedure for production of a highly purified form of recombinant human AMBN in quantities that allowed its structural characterization. Using size exclusion chromatography, analytical ultracentrifugation, transmission electron, and atomic force microscopy techniques, we show that AMBN self-associates into ribbon-like supramolecular structures with average widths and thicknesses of 18 and 0.34 nm, respectively. The AMBN ribbons exhibited lengths ranging from tens to hundreds of nm. Deletion analysis and NMR spectroscopy revealed that an N-terminal segment encoded by exon 5 comprises two short independently structured regions and plays a key role in self-assembly of AMBN.
Keywords: exony; Tooth; Dental Enamel Proteins; Extracellular Matrix Proteins; Recombinant Proteins; Exons; Amelogenin; Ameloblastin; Intrinsically Disordered Proteins; Chromatography, Gel; Microscopy, Atomic Force; elektroforéza v polyakrylamidovém gelu; Circular Dichroism; mikroskopie atomárních sil; rekombinantní proteiny; Electrophoresis, Polyacrylamide Gel; Microscopy, Electron, Transmission; konformace proteinů; cirkulární dichroismus; gelová chromatografie; nukleární magnetická rezonance biomolekulární; Protein Purification; Protein Conformation; proteiny zubní skloviny; Protein Self-assembly; transmisní elektronová mikroskopie; Nuclear Magnetic Resonance, Biomolecular